A METHOD FOR TREATING A RESIDUAL CAVITY DURING ORGAN-PRESERVING OPERATIONS FOR LIVER ECHINOCOCCOSIS WITH A RIGID FIBROUS CAPSULE (International conference on multidisciplinary science, 2024)
The study included patients with echinococcosis of the liver who had a rigid fibrous fibrous capsule. All patients were divided into two groups. The main group included 94 patients with echinococcosis of the liver, who underwent additional treatment of the residual cavity according to the proposed method during laparotomy or laparoscopic operations after the echinococcectomy stage, a total of 113 cysts were removed. Laparoscopic echinococcectomy was performed in only 8 patients in the comparison group (who had 10 cysts) and 21 patients in the main group. All the results were followed up to 3 months after the operation. There were 13 (15.9%) patients with complications in the comparison group and 2 (3.3%) in the main group.